Effectiveness of picture description education on compliance behaviors of diabetics in western Sichuan district - Rong Jiang; Min Chen; Yan Li (Elsevier, 2016)
Background: Compliance behaviors of patients are critical in the control of Type 2 diabetes. However, improving the compliance behaviors of diabetics in the western Sichuan district of China is still unclear. Objective: This study was conducted to explore the role of picture description education about their knowledge of diabetes, insulin treatment adherence, and glycogenic control level of insulin-dependent diabetic patients. Methods: A total of 182 diabetic patients who received insulin injection therapy were enrolled and randomly assigned to two groups. Patients in the control group (n = 90) received routine health education, whereas patients in the treatment group (n = 92) received picture description education based on the routine introduction about diabetes. We collected data indicating the knowledge of patients with diabetes and tested their glycogenic level one day before and three months after being discharged. Thereafter, we recorded and evaluated the changes of adherence to insulin treatment between the two groups 3 months after being discharged. Results: Knowledge of patients with diabetes, their glycogenic level, and insulin treatment adherence were significantly different in the two groups, and the data of the treatment group were better than those of the control group (p < 0.05). Conclusion: Picture description education can improve the knowledge of patients with diabetes, enhance treatment compliance, and maintain blood glucose at a desirable level.